TANGGUNG JAWAB ORANG TUA DALAM PERSPEKTIF HUKUM ISLAM DAN UNDANG-UNDANG PERLINDUNGAN ANAK DI INDONESIA - M Gamal; Aslati (STKIP Subang, 2026)
Abstract Parental responsibility toward children constitutes a fundamental aspect in shaping a high-quality generation. From the perspectives of Islamic law and Indonesia’s Child Protection Law, such responsibility encompasses the fulfillment of both material and spiritual needs, religious education, moral development, and guardianship. This study aims to analyze these forms of responsibility comprehensively using a normative approach through literature review. The findings reveal that Islamic law and Indonesian statutory regulations are aligned in positioning parents as the primary actors responsible for ensuring the physical, spiritual, and moral well-being of children. However, challenges remain in their implementation, particularly in fulfilling spiritual needs and moral education amid ongoing social changes. Therefore, synergy among families, communities, and the state is essential to ensure the optimal fulfillment of children’s rights.